The Influence of Leadership, Organizational Commitment, and Work Motivation as Intervening Variables on Job Satisfaction of ASN Employees - Awang Adin Nugroho; Ahmad Badawi Saluy (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the factors that influence job satisfaction of ASN employees of the DKI Jakarta Province Education Office. The benefit of this research is to solve the problem of job satisfaction of ASN employees of the Jakarta Province Education Office. The population of this study were ASN employees at Jakarta Province Education Office with a sample size of 130 employees with an observation period of 2024. The dependent variable in this study is job satisfaction, while the independent variables used are leadership and organizational commitment, with the intervening variable used is work motivation. This research is a quantitative research with data analysis method using Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that leadership and organizational commitment have a positive and significant effect on work motivation, leadership and organizational commitment have a positive and significant effect on job satisfaction, transformational leadership and organizational commitment have a positive and significant effect on job satisfaction through work motivation.